Transcatheter edge-to-edge-repair of functional mitral regurgitation induces significant remodeling of mitral annular geometry - Paukovitsch, Michael; Felbel, Dominik; Jandek, Madeleine; Keßler, Mirjam; Rottbauer, Wolfgang; Markovic, Sinisa; Groeger, Matthias; Tadic, Marijana; Schneider, Leonhard Moritz (Frontiers in Cardiovascular Medicine, 2023)
Background Mitral annular alterations in the context of heart failure often lead to severe functional mitral regurgitation (FMR), which should be treated with transcatheter edge-to-edge repair (M-TEER) according to current guidelines. M-TEER's effects on mitral valve (MV) annular remodeling have not been well elucidated. Methods 141 consecutive patients undergoing M-TEER for treatment of FMR were included in this investigation. Comprehensive intraprocedural transesophageal echocardiography was used to assess the acute effects of M-TEER on annular geometry. Results Average patient age was 76.2 ± 9.6 years and 46.1% were female patients. LV ejection fraction was reduced (37.0% ± 13.7%) and all patients had mitral regurgitation (MR) grade ≥III. M-TEER achieved optimal MR reduction (MR ≤ I) in 78.6% of patients. Mitral annular anterior-posterior diameters (A-Pd) were reduced by −6.2% ± 9.5% on average, whereas anterolateral-posteromedial diameters increased (3.7% ± 8.9%). Overall, a reduction in MV annular areas was observed (2D: −1.8% ± 13.1%; 3D: −2.7% ± 13.7%), which strongly correlated with A-Pd reduction (2D: r = 0.6, p < 0.01; 3D: r = 0.65, p < 0.01). Patients that achieved A-Pd reduction above the median (≥6.3%) showed significantly lower rates of the composite endpoint rehospitalization for heart failure or all-cause mortality than those with less A-Pd reduction (9.9% vs. 28.6%, p = 0.037, log-rank p = 0.039). Furthermore, patients reaching the composite endpoint had an increase in annular area (2D: 3.0% ± 15.4%; 3D: 1.9% ± 15.3%), whereas those not reaching the endpoint showed a decrease (2D: −2.7% ± 12.4%; 3D: −3.6% ± 13.3%), although residual MR after M-TEER was similar between these groups (p = 0.57). In multivariate Cox regression adjusted for baseline MR, A-Pd reduction ≥6.3% remained a significant predictor of the combined endpoint (OR: 0.35, 95% CI: 0.14–0.85, p = 0.02). Conclusion Our findings indicate that effects of M-TEER in FMR are not limited to MR reduction, but also have significant impact on annular geometry. Moreover, A-Pd reduction, which mediates annular remodeling, has a significant impact on clinical outcome independent of residual MR.